AN ANALYSIS ON THE EIGHTH STUDENTS’ PERCEPTION OF THE APLICATION PPP (PRESENTATION, PRACTICE AND PRODUCTION) TECHNIQUE IN TEACHING WRITING DESCRIPTIVE TEXT - Frisca Nadya Tarina; Yana Yana (IKIP Siliwangi, 2021)
Based on the phenomena that students have difficulties in writing descriptive text, the students could not write because they do not have any ideas when they are asked to write. So, they need some ways which could help them in writing. The problems in writing can be solved by implementing some strategies in teaching writing. This research aims at knowing the use of PPP (Presentation, Practice and Production) in teaching writing to the eighth grade students. This research is qualitative research. The subject of this research was the eighth grade students of one junior high school in Cimahi in the academic year of 2020 – 2021 which consisted of 31 students. The writer used a questionnaire to collect data. These findings reveal that the use of PPP (Presentation, Practice and Production) techniques in teaching writing in the classroom can improve students' writing abilities in the classroom. Based on the result of questionnaire the use of PPP (Presentation, Practice and Production) one of the right way to teach writing. It means that using make a match method was effective, and easier to be applied in teaching writing descriptive text. Keywords: PPP (Presentation, Practice and Production), Teaching Writing, Students’ Ability